Morphological and molecular characterization of Strongyloides ophidiae (Nematoda, Strongyloididae) - dos Santos, K. R.; Carlos, B. C.; Paduan, K. S.; Kadri, S. M.; Barrella, T. H.; Amarante, M. R. V. [UNESP]; Ribolla, P. E. M. [UNESP]; da Silva, R. J. [UNESP] (Cambridge University Press, 2010)
The aim of the present study is to report morphological data from parasitic female, rhabditoid and filarioid larvae, free-living female worms and eggs of Strongyloides ophidiae (Nematoda, Strongyloididae). In addition, a molecular DNA analysis was carried out using a pool of eight S. ophidiae parasitic females. Samples were obtained from the small intestine of Oxyrhopus guibei (Serpentes, Colubridae) collected in the municipality of Lencois Paulista, State of São Paulo, Brazil. DNA amplification by polymerase chain reaction (PCR) resulted in a 350 bp band for samples containing S. ophidiae and Strongyloides venezuelensis DNA. Strongyloides ophidiae nucleotide sequence analysis showed 98% similarity with Strongyloides procyonis and 97% with Strongyloides cebus, Strongyloides stercoralis, Strongyloides fuelleborni and Strongyloides sp. from snakes.